Determination of oseltamivir in human plasma by HPLC-MS/MS - Lakeev, Alexander P.; Abdrashitova, N. Yu; Bryushinina, O. S.; Frelikh, Galina A.; Tsuran, D. V.; Zyuzkova, Yu. G.; Udut, Vladimir V. (Pharmaceutical chemistry journal)
A procedure for the determination of oseltamivir in human plasma by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) was proposed and validated. A rapid and easy-to-use method of liquid-liquid extraction with ethyl acetate using venlafaxine as an internal standard was used during sample preparation. The addition of benzoic acid to aqueous acetonitrile solutions of the analyte was shown to prevent its oxidative degradation. The detection limit and limit of quantitation were 0.08 and 0.30 ng/mL, respectively; the calibration range, 0.3-200 ng/mL (R2 = 0.9937); the total analysis time, 3.2 min. The within- and between-run accuracy ranged from 97 to 105%. The precision was <10%. The proposed procedure was characterized by selective determination of the analyte, the absence of significant matrix effects, the ability to dilute samples with high analyte concentrations, and satisfactory extraction recovery (>89%). The analyte was stable when stored in plasma samples (4 h at room temperature, 31 d at (80°C, after three freeze-thaw cycles) and extracts under autosampler storage conditions (24 h at 15°C). The procedure was successfully used for oseltamivir quantitation in actual plasma samples from healthy volunteers obtained during a bioequivalence study of the new generic drug.